PRE AND POSTOPERATIVE PH MONITORING AND WEIGHT LOSS ANALYSIS IN PATIENTS UNDERGOING GASTRIC PLICATION IN ASSOCIATION WITH FUNDOPLICATION - IVANO,Flávio Heuta (2017)
ABSTRACT Background : Obese patients with gastroesophageal reflux disease with pathological pH monitoring result may benefit from surgical treatment which is based on the fundoplication technique in association with laparoscopic gastric plication. The Nissen surgery is the gold standard for surgical treatment of gastroesophageal reflux disease, whereas laparoscopic gastric plication is a restrictive surgery that consists of the invagination of the greater curvature, resulting in weight loss. Aim: To compare pre and postoperative pHmetry results and to evaluate weight loss in patients submitted to gastroplasty with fundoplication. Method: Sixteen patients with class I body mass index with symptoms of gastroesophageal reflux with changes of stomach pH and/or erosive esophagitis seen in endoscopy were selected The evaluation of the weight and 24-h pH monitoring was performed preoperatively and postoperatively. The weight, body mass index, percentage of excess weight loss and DeMeester score of patients that underwent the surgery were evaluated pre and postoperatively. Results: Regarding pH monitoring, the average preoperative DeMeester index was 28.7, which was followed by a significant postoperative average reduction to 2.8 (p<0,001). Regarding the weight reduction, the average of weight loss was 13.6 kg and body mass index of 5.3 kg/m2 (p<0.001). Furthermore, the average percentage of excess weight loss was 53.9% (standard deviation=26.2). Conclusion: The combination of Nissen surgery and gastric plication is a viable procedure and appears to be an acceptable option for the treatment of gastroesophageal reflux disease in obese patients, especially patients with obesity class I.